A comparative study on the crucial parameters for soundless chemical crushing efficiency of reinforced concrete shear wall: Experimental and theoretical investigation. (11th January 2023) - Li, Ruisen; Zheng, Wenzhong; Tian, Weichen; Yan, Yu; Li, Guangchao
Highlights: A new method to evaluate soundless chemical crushing efficiency of shear walls was proposed. The effects of crushing design and structural parameters on soundless chemical crushing were investigated. The rationality of total crack widths and fractal dimension as evaluation indicators was compared. An exponential relationship between the structural characteristic value and fractal dimension was established. Abstract: Soundless chemical demolition as an environment-friendly demolition method has been widely researched in the field of rock and plain concrete breakage due to their brittle characteristic. However, the utilization of this method on reinforced concrete structures was limited and should be further researched to broaden its application in the building demolition area. This study gave a thorough research concerning the effect of soundless chemical demolition on crushing reinforced concrete shear walls. Experimental results showed that the number of distributed reinforcements played a more significant role in the development of cracks than the reinforcement diameter. Further, the walls with vertical holes showed a higher crushing degree and efficiency compared with inclined holes, indicating the crucial role of drilling types. Moreover, a structural characteristic value was introduced based on the dimensional analysis to describe the arrangement of distributed reinforcement inside the shear walls, and the fractal theory was further utilized to illustrate the overall crushing degree of the structures. An exponential relationship between the structural characteristic value and fractal dimension can be observed, leading to the theoretical prediction of the crushing degree for reinforced concrete shear walls with soundless chemical demolition.